Responsive nanoparticles synergize with Curcumin to break the “reactive oxygen Species-Neuroinflammation” vicious cycle, enhancing traumatic brain injury outcomes - Xianhua Fu; Yongkang Zhang; Guojie Chen; Guangyao Mao; Jiajia Tang; Jin Xu; Yuhan Han; Honglin Chen; Lianshu Ding (Journal of Nanobiotechnology)
Abstract Traumatic brain injury (TBI) disrupts oxygen homeostasis in the brain, leading to excessive reactive oxygen species (ROS) production and dysregulated antioxidant mechanisms, which fail to clear excess ROS. This ROS overload promotes the expression of pro-inflammatory genes, releasing cytokines and chemokines and creating a vicious “ROS-neuroinflammation” cycle, making it essential to break this cycle for effective TBI treatment. In this study, we developed cysteine-alanine-glutamine-lysine (CAQK) peptide-modified antioxidant nanoparticles (C-PPS/C) for co-delivery of curcumin (Cur) to modulate oxidative and neuroinflammatory disturbances after TBI. In TBI mice, C-PPS/C nanoparticles accumulated in injured brain regions, where poly (propylene sulfide)120 scavenged ROS, reducing oxidative stress, while Cur release further suppressed ROS and inflammation. C-PPS/C nanoparticles broke the “ROS-neuroinflammation” cycle, protecting the blood-brain barrier (BBB), reducing acute brain edema, and promoting long-term neurological recovery. Further investigation showed that C-PPS/C nanoparticles inhibited the NF-κB pathway, reducing pro-inflammatory gene expression and mitigating inflammation, suggesting a promising approach for TBI treatment.